2019
DOI: 10.2298/pan160409022b
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of merchandise trade flows between Croatia and other EU member states: Panel cointegration approach

Abstract: This research examined the sustainability of merchandise trade flows between Croatia and other European Union (EU) member states. Merchandise exports and imports were disaggregated into bilateral merchandise trade flows between Croatia and nineteen EU trading partners for the period 1999-2014. Following Granger-causality and cointegration tests for panel data, we specified the model to be estimated. Using a pooled mean group (PMG) estimator for dynamic heterogeneous panel data, the relationship between Croatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Ismaili-Muharremi (2015) analysed the current account of Western Balkan countries (Albania, Kosovo, Macedonia, Bosnia and Herzegovina, Serbia, Montenegro) and pointed out that the sustainability of the current account remains the most challenging macroeconomic issue for all these countries. Bošnjak et al (2018a) found merchandise trade flows between Croatia and other EU member countries unsustainable. Consistently with results from Haltmaier (2014), Bošnjak et al (2018) explained the Croatian path from deficit to current account surplus and pointed out the asymmetric responses of the Croatian current account to changes in domestic demand and money supply.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Ismaili-Muharremi (2015) analysed the current account of Western Balkan countries (Albania, Kosovo, Macedonia, Bosnia and Herzegovina, Serbia, Montenegro) and pointed out that the sustainability of the current account remains the most challenging macroeconomic issue for all these countries. Bošnjak et al (2018a) found merchandise trade flows between Croatia and other EU member countries unsustainable. Consistently with results from Haltmaier (2014), Bošnjak et al (2018) explained the Croatian path from deficit to current account surplus and pointed out the asymmetric responses of the Croatian current account to changes in domestic demand and money supply.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Following VECM, Franc and Peulić (2017) found cointegrated relationship between exports and imports in case of Slovenia while the import to export pattern was detected as the one that dominated. Bošnjak et al (2018) followed panel cointegration approach and found the weakly sustainable pattern of international trade between Croatia and other EU member countries. Following the presented literature, there is no common conclusion regarding the relationship between exports and imports.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The merchandise trade between Croatia and other E.U. member countries was found unsustainable (Bo snjak, Bilas, & Novak, 2019) and well explained by the Heckscher-Ohlin trade theorem, while Croatia appeared as the labour abundant country (Bilas & Bo snjak, 2015b). Boljanovi c (2012) analyzed the current account deficit in Serbia and pointed out that industrial production in Serbia heavily depends on imported goods financed by inflow of foreign capital.…”
Section: Introductionmentioning
confidence: 99%